Pengaruh Implementasi Model Pendidikan Islam Holistik terhadap Pembentukan Karakter dan Prestasi Siswa di MIN 2 Labuhanbatu - Siti Aminah Hasibuan; Ismi Yulizar; Yuli Yani; Eriani; Dwina Putri (Insan Zenius Ilmiah, 2025)
This study aims to analyze the effect of the implementation of a holistic Islamic education model on character formation and student achievement at MIN 2 Labuhanbatu Rantauprapat. Holistic Islamic education is an approach that emphasizes the integration of spiritual, intellectual, and social values ​​in the learning process, which is believed to be able to shape a child's personality that is balanced and has noble morals. This study uses a quantitative approach with a correlational study design. The study population was 100 students, with a sample of 30 students taken through a saturated sampling technique from class VA consisting of 15 boys and 15 girls. Data collection was carried out using a questionnaire instrument designed based on indicators of holistic Islamic education, covering cognitive, affective, spiritual, and social aspects. Data analysis was conducted to examine the relationship between the implementation of holistic Islamic education and character formation and student achievement. The results of the study indicate that the implementation of a holistic Islamic education model has a significant effect on character formation and improving children's learning achievement. These findings reinforce the urgency of a comprehensive educational approach based on Islamic values ​​in early childhood education. The implications of the results of this study are expected to be a strategic reference for educational institutions and policy makers in designing integrative, contextual, and sustainable learning models.